Instrumental Activity of Daily living in war related bilateral lower limb amputation - M.R. Soroush; Z. Ganjparvar; M. Masoumi; B. Mousavi (طب جانباز, 2012)
Objective(s): Independency in life activities has an important role in individuals with disability to bring them back to normal life. The objective of this study was to determine Instrumental Activity of daily Living in survivors of the Iran-Iraq war with bilateral lower limb amputation.